Multimedia Interaktif untuk Pembelajaran Sinematografi - Miyarso, Estu (MAJALAH ILMIAH PEMBELAJARAN, 2009)
In general this study aims to reveal: (1) Developing of interactive multimedia product on CD program form for the study of cinematography, and (2) The effectiveness of interactive multimedia. The tryout subjects in this study were 35 people consisting of 2 content expert, 2 instructional media specially, 3 students in one-to-one evaluation, 8 students in small group experiment, and 20 students in field experiment. The data were collected of formative evaluation done using assessment enquette for the aspect of instruction, content, design, and pemrogramming. The data collected sumative evaluation done using pretest and posttest and also enlist interview and cheque. The result findings show that: (1) Product of interactive multimedia for The Study of Cinematography have been developed in the form of the CD program as according to development procedure. This matter proven that; product quality of interaktive multimedia of instruction aspect is in good criterion with the average score 3,92; content aspect is in good criterion with the average score 3,65; design aspect is in good criterion with the average score 3,74; and programming aspect is in good criterion with the average score 3,73. (2) The product of interactive multimedia used effective for The Study of Cinematography, proven by increase of score average of pretest and posttest from students equal to 9,55 or 14,54% in once meeting. Besides, data result of interview and observation of that product can motivate students at the process study of.